Fundamentals of corporate finance - Ross, Stephen A. (McGraw-Hill, 2012)
This texts builds on the tradition of excellence that instructors and students have come to associate with the Ross, Westerfield and Jordan series. It blends comprehensive coverage of modern research with an emphasis on practical applications. Written with one strongly held principle that corporate finance should be developed and taught in terms of a few integrated, powerful ideas, three basic themes became the central focus of the book. This Asia Global Edition aims to meet the significant gap for a book with Asian examples and internationalized Asian content. -- From back cover.